SplitAx: A novel method to assess the function of engineered nucleases. - Richard A Axton; Sharmin S Haideri; Martha Lopez-Yrigoyen; Helen A Taylor; Lesley M Forrester (PLoS ONE)
Engineered nucleases have been used to generate knockout or reporter cell lines and a range of animal models for human disease. These new technologies also hold great promise for therapeutic genome editing. Current methods to evaluate the activity of these nucleases are time consuming, require extensive optimization and are hampered by readouts with low signals and high background. We have developed a simple and easy to perform method (SplitAx) that largely addresses these issues and provides a readout of nuclease activity. The assay involves splitting the N-terminal (amino acid 1-158) coding region of GFP and an out-of-frame of C-terminal region with a nuclease binding site sequence. Following exposure to the test nuclease, cutting and repair by error prone non-homologous end joining (NHEJ) restores the reading frame resulting in the production of a full length fluorescent GFP protein. Fluorescence can also be restored by complementation between the N-terminal and C-terminal coding sequences in trans. We demonstrate successful use of the SplitAx assay to assess the function of zinc finger nucleases, CRISPR hCAS9 and TALENS. We also test the activity of multiple gRNAs in CRISPR/hCas9/D10A systems. The zinc finger nucleases and guide RNAs that showed functional activity in the SplitAx assay were then used successfully to target the endogenous AAVS1, SOX6 and Cfms loci. This simple method can be applied to other unrelated proteins such as ZsGreen1 and provides a test system that does not require complex optimization.